Recent Developments in the Suzuki-Miyaura Reaction: 2010–2014 - Irene Maluenda; Oscar Navarro (Molecules, 2015)
The Suzuki-Miyaura reaction (SMR), involving the coupling of an organoboron reagent and an organic halide or pseudo-halide in the presence of a palladium or nickel catalyst and a base, has arguably become one of most utilized tools for the construction of a C-C bond. This review intends to be general account of all types of catalytic systems, new coupling partners and applications, including the literature between September 2010 and December 2014.